A comparative analysis of the abnormal returns made by acquirers in acquisitions on the Johannesburg Stock Exchange South Africa (JSE) - Monnakgotla, Zanele (My University, 2015)
The purpose of the study is to investigate how a changed economic environment caused by the financial crisis and global recession in 2008 impacted the abnormal returns made by shareholders in acquisition transactions in South Africa. This was done by means of a review of acquisitions in South Africa and comparing the abnormal returns made in transactions executed pre-financial crisis (2003-2007) with those made post financial crisis (2008-2013). The study also investigated whether the form of payment (ie cash funded or stock funded) for the acquisition affected the abnormal returns. The event study method which is the most dominant method (Martynova and Renneboog 2008) was used. An event period of 14 days was used with a pre- merger period 8 days prior to the announcement and post-merger period being 5 days after the announcement of the merger. The main research findings was that where the acquirers in SA were listed companies, the acquirers in the short term, made negative abnormal returns. This finding is aligned to a number of findings in the UK such as Dodd (1980) and Firth (1980) as well as the majority studies in the USA, where significantly negative returns to acquirers were found in research by Draper and Paudyal (1999) , Mulharin and Boone (2000). Where the acquirers investigated are unlisted they made positive abnormal returns in the short term, as was the case in SA Affleck-Graves,Flach and Jacobson (1988) and the UK, Asquith and Kim (1982), Jensen and Ruback (1983). The explanation for this divergence in findings according to Fuller et al (2002) is that unlisted acquirers make higher returns than listed ones. The finding of negative short term abnormal returns for acquirers’ is aligned to findings of more recent studies (i.e1990’s and 2000 to current) in developed economies such as the USA and the UK as stated above. Similar finding of negative returns to acquirers in the US , UK and South Africa can be explained in a number of ways. Firstly South Africa has developed capital and equities markets that have strong linkages with the UK (Yartey and Adjasi 2007).The effect of the transmission mechanism on the South African bond and equities market , lastly current literature on M&A’s also finds strong correlation in legal systems and returns to shareholders in M&A transactions, (La Porta et al 1997 and 2000) with SA and UK both using the English common law. Another interesting finding was that abnormal returns earned by acquirers post crisis are higher than those earned by acquirers pre- crisis. This finding was unexpected and can be explained by the fact that post crisis the volume of companies in distress and in liquidation increased by 18% (peaking to 4133 liquidations) from 2003 to 2009 (Statistics South Africa 2010).As there was a higher volume of companies in distress, acquirers were in a stronger bargaining position and could thus negotiate more reduced purchase prices for the target. 6 One other interesting finding is that cash funded acquisitions higher abnormal returns than the stock funded acquisitions. The cash funded M&A’s also increase substantially in number to make up 81 percent of acquisitions post crisis. On reviewing our literature review we find that this finding is contrary to that made was made also by Kaufeler (2012), and Seghal (2012) wherein returns before the financial crisis found that cash payments generated higher returns for acquirers and post financial crisis the stock payments generated higher returns for acquirers. This research does not confirm the finding by Seghal (2012) and Kaufeler 2012) that there has been a change in sentiment on cash and stock funded M&A and that post the 2008 financial crisis stock funded acquisitions are perceived as value creating and cash funded transactions are perceived as value destroying. Seghal (2012) explains this change in sentiment by investors in emerging countries by using the “free cashflow hypothesis” wherein the investors see lots of investment opportunities for companies in these markets and thus prefer the cashflow to be used to fund these investment opportunities. Another hypothesis that is used to explain this change in sentiment is the asymmetry of information hypothesis wherein it is assumed that there is higher asymmetry of information in emerging markets and that the funding of acquisitions with stock shall reduce the risk to the acquirer as the target also takes a higher risk with a share acquisition. In South Africa another aspect that could have influenced investors’ change in sentiment towards cash, post crisis, is the tighter regulations for the granting of credit which was effected by the passing of the National Credit Act 1 herein after referred to as “the Act”) .The Act was effective from June 2006 and was in full force and effect in 2007.Even though the Act applies to credit transactions of less than R1million it still could have had the effect of changing sentiments. The conclusion of this research is that the study has achieved its objective which was to analyse and investigate whether there are any patterns and trends that transpire on M&A’s pre and post financial crisis, whether there are any significant changes in returns for acquirers. This study bears evidence that for South African listed firms, post financial crisis acquirers’ have earned higher abnormal returns than pre-crisis as this is shown by the AR, AAR’.s and CAAR’s (see table 6).This finding corroborates the anecdotal evidence by Ernst and Young (2009) that post financial crisis acquiring companies created more value post crisis than the acquirers that effected their acquisitions pre-crisis. This could be largely due to there being more opportunities post crisis to acquire a company in financial distress and to negotiate a higher discount on the purchase price as there was an increase in the number of companies in financial stress. Further analysis is required to investigate investors’ preferred mode of funding M&A’s in South Africa and other emerging countries. In the research more emerging countries especially African countries must be analysed, and a longer period of analysis is required in order to validate whether for emerging markets the most preferred mode of funding 1 Act no 34 of 2005 7 acquisitions for investors is through stock acquisitions .This investigation is very important as it would help shareholders and executives, to better align their acquisitions with investors’ preferences so as to make better returns on these transactions. The contribution of this study is to update and add to the knowledge of M&A’s in South Africa as in most of the literature it was stated that there is insufficient research of M&A’s in emerging countries especially on African countries ( Ma et al 2009) as most of the research is on developed economies. This study updates current South African literature on the latest trends in M&A’s in South Africa. It sheds some light on the factors driving these trends, it also clearly illustrates areas of commonality and those of divergence in M&A’s in emerging markets and developed economies. The recent global financial crisis has made this research more relevant as there has been more turbulence in the global economy due to the crisis. The financial and economic environment is very dynamic and investors, shareholders, asset managers and policy makers have to be constantly informed of the latest trends so that the can make better investments and policy makers can effect better policies.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.